A Myc-driven self-reinforcing regulatory network maintains mouse embryonic stem cell identity - Luca Fagnocchi (Nature Portfolio, 2016)
The Myc transcription factor is a major regulator of stem cell (SC) self-renewal and pluripotency but how this integrates signals from other pathways is unclear. Here, the authors show that Myc activation triggers epigenetic memory in self renewing embryonic SCs via PRC2-mediated potentiation of the Wnt pathway.